PEDAGOGIKA FANINING TA’LIM MAZMUNI VA ASOSIY YO‘NALISHLARI - Mustafayev, Sh.N. (SCIENCE and SOCIETY, 2024)
In this scientific article, five main applications of pedagogy as a science are discussed, including education and upbringing in pedagogical practice, acquiring pedagogical skills, pedagogical systems, technology, pedagogical engineering, pedagogical principles, the main rules of pedagogy as a science and their application, forming professional pedagogical views on life among students, types of education, the unique meanings of education, conceptual apparatus, principles, laws, and technologies of education.
Keywords: modernization; pedagogical practice; pedagogical skills; pedagogical engineering; pedagogical technology; pedagogical principles; knowledge; skill; ability; competence; pedocentric; sociocentric; type of education; meaning of education